Precarização e escravidão contemporâneas: reforma trabalhista, direitos fundamentais e dignidade humana – das promessas ao desencantamento - RAMOS, Fernanda Franklin da Costa (2023)
The main objective of the research is to analyze aspects and impacts resulting from the Labor Reform in the Worker Protection Justice System, regarding the fight against the practice of reducing workers to conditions analogous to slavery, with a focus on access to Justice and fundamental social rights, and rule of law. The theoretical framework consists of the conceptualization of the social value of work shaped by the dignity of the worker, considered as a fundamental precept, from the perspective of Chai (2004), in concurrent protection by international norms of universal human rights. It discusses the emptying of repressive practices that mitigate the reduction to a condition analogous to slavery and the rule of slavery as a measure of the underdevelopment of a society. Bibliographical and documentary reviews are adopted as methodological procedures, as well as the use of qualitative and quantitative research and the deductive method in the analysis of judicial decisions in which there is an allegation of work in conditions analogous to slavery filed at the Regional Labor Court of the 16th Region, in the time frame from 2017 to 2022, and the perceived impacts on the demands arising from Law 13,467/2017, with the violation of fundamental social rights. Among others, there are works by the following authors: Sen (2010), Chai (2004), Moura (2023), Farias (2022), Rawls (2011), Delgado (2017) and Jacob (2016). With the results achieved, it is demonstrated that the practice of exploiting workers in conditions analogous to slavery did not decrease during the research period, with its judicial repairs having been hampered as a result of the labor reform. It is concluded that the objectification of the human being is an inadmissible conduct, and the institutions of the justice system, society and academia, as mechanisms for transforming the world, must unite with the aim of preserving the dignity of the human person, fighting the work in conditions analogous to slavery and the violation of hard-won rights through great class efforts, achieved through legal instruments such as labor reform.